THE ROLE OF PERSONS WITH DISABILITIES IN POLITICAL EDUCATION AND AWARENESS OF POLITICAL PARTICIPATION - Yusnelli Yusnelli; Irwan Irwan; Nofridayati Nofridayati; Ade Syahputra; Bambang Wijaksana (Adisam Publisher, 2025)
The purpose of this study is to find out The Role of Persons with Disabilities in Political Education and Awareness of Political Participation. The method of this research is descriptive, analytical, and critical. Therefore, the author can provide a comprehensive description of the Role of Persons with Disabilities in Political Education and Awareness of Political Participation. In this study, the author optimally uses two data sources related to this research, namely. Primary data sources and secondary data sources. The results of this study indicate that political awareness among people with disabilities is on the rise. However, challenges in terms of accessibility and support still significantly hinder their participation. Sustained efforts from governments, election organizers, and the public are needed to create an inclusive political environment and support the active involvement of people with disabilities.